The Scythian Empire: Central Eurasia and the Birth of the Classical Age From Persia to China. By Christopher I. Beckwith. - Rubinson, Karen S (Journal of Church & State)
Christopher Beckwith's book, "The Scythian Empire: Central Eurasia and the Birth of the Classical Age From Persia to China," challenges traditional views on the emergence of a Scythian empire in Central Eurasia. Beckwith argues that the Scythians played a pivotal role in shaping the Classical Age through their language, philosophies, and monotheistic religions. While his work is innovative, scholars question his generalizations and the transference of ideas primarily through direct domination. Beckwith's concept of a Scythian empire based on divine leadership lacks archaeological evidence and overlooks the diversity of populations during that period.